Current Status Of Organization Of Finished Products Accounting At Regional Light Industry Enterprises (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article analyzes the current state of organization of finished products accounting at regional light industry enterprises from a scientific and practical perspective. It covers the role of light industry in the economy, the content of the concept of finished products in accounting, the current regulatory and legal framework, accounting for the acceptance, storage, registration and sale of finished products in the warehouse. Also, existing problems related to document circulation, inventory, calculation, account registers, digitization and automation at regional enterprises are analyzed and scientifically based proposals are presented for their elimination
Keywords: Light industry; regional enterprise; finished products; accounting